Evaluating irrigation investments in Malawi: economy‐wide impacts under uncertainty and labor constraints - Schuenemann, F.; Thurlow, James; Meyer, S.; Robertson, R.; Rodrigues, J. (Wiley, 2018)
Irrigation expansion is critical to increase crop yields and mitigate effects from climate change in Sub‐Saharan Africa, but the low profitability has led to little irrigation investments in the region so far. Using an integrated modeling framework, we simultaneously evaluate the returns to irrigation arising from both economic and biophysical impact channels to understand what determines the profitability of irrigation in Malawi. Our results confirm that the returns to irrigation cannot cover the costs in Malawi. While labor‐intensive irrigation expansion leads to unfavorable structural change in the short‐run, the profitability hinges on low irrigated yields that fall far from expectations due to insufficient input use and crop management techniques. On the other hand, we find that the nonmonetary benefits of irrigation regarding higher food security, lower poverty, and reduced vulnerability to climate change make investments in irrigation worthwhile to improve the livelihoods of smallholders.